1995
DOI: 10.1108/00070709510077944
|View full text |Cite
|
Sign up to set email alerts
|

Poland′s fruit industry in transition

Abstract: Examines the development of Poland′s fruit industry up to 1990, followed by the situation since that year, in which legislative reforms were introduced, mainly to break up state monopolies and to privatize state assets. Analyses the Polish fruit industry in the light of the resultant shift from a sellers′ to a buyers′ market, discussing the grower, wholesaling, processing and exporting sectors, and finally the role of marketing in exporting. Conducts a SWOT analysis of the industry, as a result of which makes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…This process was influenced by the fact that foreign partners used to have a very limited knowledge of the Polish business environment and they were interested in obtaining a firm having a stable market position, which reached a certain limit of development which could not be overcome due to the shortage of capital for further investment enabling new dynamics of growth. Additional barriers to development of food companies in Poland were due to weak infrastructure (Faesel and Hill, 1995).…”
Section: The Role Of Foreign Partners In the Company Developmentmentioning
confidence: 99%
“…This process was influenced by the fact that foreign partners used to have a very limited knowledge of the Polish business environment and they were interested in obtaining a firm having a stable market position, which reached a certain limit of development which could not be overcome due to the shortage of capital for further investment enabling new dynamics of growth. Additional barriers to development of food companies in Poland were due to weak infrastructure (Faesel and Hill, 1995).…”
Section: The Role Of Foreign Partners In the Company Developmentmentioning
confidence: 99%
“…The review of the SWOT literature shows that Faesel and Hill (1995) were the first to use SWOT analysis in the agricultural field. They found that because of the weak infrastructure in Poland, the development of the food business was hard.…”
Section: Agriculturementioning
confidence: 99%
“…They found that because of the weak infrastructure in Poland, the development of the food business was hard. Since Faesel and Hill's (1995) work, many studies utilizing a SWOT analysis have been published in the agricultural sector, particularly in developing countries.…”
Section: Agriculturementioning
confidence: 99%
“…The fi rst work in this fi eld is a paper by Faesel and Hill (1995), though using SWOT in agriculture prevailed almost since 2002 and many papers published since then. An interesting point is that these papers are mostly belonging to developing countries (particularly India) and them often assessing agriculture condition in a specifi c geographic region rather than strategic positioning of a special organization.…”
Section: Agriculturementioning
confidence: 99%